Early outcomes of drug-coated balloon angioplasty and stent placement for the treatment of iliac artery lesions - Wen, Jia-Hao; Li, Chun-Min; Jin, Zhen-Yi; Wang, Sheng-Xing (Frontiers in Surgery, 2025)
ObjectiveThe efficacy and safety of drug-coated balloons (DCBs) in the treatment of aortoiliac artery stenosis or occlusion remains poorly explored.MethodsA single-center retrospective cohort study of patients diagnosed with iliac artery stenosis or occlusion who received either iliac artery DCB angioplasty or stent implantation was conducted at our institution. The patients were followed up 6 and 12 months postoperatively. Lower limb computed tomography angiography was performed during the follow-up period. The primary endpoint of the study was the primary patency at 6 and 12 months. Both the clinical and follow-up data were analyzed.Results50 patients underwent DCB angioplasty, while 71 received stent implantation. Demographic and lesion characteristics were comparable between the two groups (P > 0.05). However, the balloon diameter used in the DCB group was significantly smaller (6.42 ± 0.80 mm vs. 7.39 ± 0.97 mm, P < 0.001). The primary patency values 6 and 12 months postoperatively were 84.2% and 80.7% for the DCB group and 96.1% and 89.6% for the stent group, respectively with no significant difference between the two groups (P = 0.124). However, the 12-month patency in the common iliac artery segment for the DCB group was significantly lower than that for the stent group (75.0% vs. 97.3%, P = 0.006). Univariate and multivariate logistic analyses did not identify any factors associated with long-term patency.ConclusionSame as stents, DCBs maintained a favorable but lower patency rate across various calcification levels and different TASC Ⅱ classification in patients with aortoiliac artery stenosis or occlusion.